A beetle antennae search improved BP neural network model for predicting multi-factor-based gas explosion pressures. (May 2020) - Xu, Ying; Huang, Yimiao; Ma, Guowei
Abstract: A gas explosion in an underground structure may cause serious damage to the human body and ground buildings and may result in huge economic losses. The pressure of the gas explosion is an important parameter in determining its severity and designating an emergency plan. However, existing empirical and computational fluid dynamics (CFD) methods for pressure prediction are either inaccurate or inefficient when considering multiple influencing factors and their interrelationships. Therefore, for a more efficient and reliable prediction, the present study developed a multifactorial prediction model based on a beetle antennae search (BAS) algorithm improved back propagation (BP) neural network. A total of 317 sets of data which considered factors of geometry, gas, obstacle, vent, and ignition were collected from previous studies. The results showed that the established model can predict pressures accurately by low RMSE (43.4542 and 50.7176) and MAPE (3.9666% and 4.9605%) values and high R 2 (0.7696 and 0.7388) values for training and testing datasets, respectively. Meanwhile, the BAS algorithm was applied to improve both the calculation efficiency and the accuracy of the proposed model by enabling a more intelligent hyperparameter tuning method. Furthermore, the permutation importance of input variables was investigated, and the length (L) and the ratio of length and diameter (L/D) of geometry were found to be the most critical factors that affect the explosion pressure level. Highlights: This study proposes a multi-factor-based prediction model of gas explosion pressures. The model employs a beetle antennae search (BAS) algorithm to tune the back propagation (BP) neural network. This proposed model may allow a more accurate and efficient pressure prediction. The L and L/D of geometry are most critical factors that affect the explosion pressures.